(untitled) (Research, Society and Development, 2022)
Overweight and obesity are becoming more frequent worldwide. According to the World Health Organization (WHO), the global prevalence of obesity has almost tripled since 1975. Diet-induced obesity is a major aspect of the modern sedentary lifestyle, eating habits and metabolic dysfunctions described globally as the syndrome of cardiometabolic risk. So far, some phytochemicals derived from edible natural resources have been found to have a promoting effect on thermogenic adipocytes. These natural compounds, such as lycopene, mangiferin, cyanidin-3-glycoside, gingerol and baicalin were reported to activate adipocyte thermogenesis through the regulation of different signaling pathways. compounds in the context of obesity. This is an integrative literature review, built from the following steps: elaboration of the guiding question, search or sampling in the literature, data collection, critical analysis of the included studies, discussion of the results and presentation of the integrative review. The search and selection process resulted in the eligibility of 5 articles. The results reported by each study indicate that the presence of some phytochemicals in the diet can prevent body weight gain, remodeling the body’s energy metabolism through different mechanisms of action such as activation of functional thermogenic genes, induction of the gamma 1 alpha coactivator of the receptor activated by peroxisome proliferator (PGC1α), increased respiratory exchange and heat production from adipose tissue.